Citizens in the Graeco-Roman World (Brill, 2017)
The twelve studies contained in this volume discuss some key-aspects of citizenship from its emergence in Archaic Greece until the Roman period before AD 212, when Roman citizenship was extended to all the free inhabitants of the Empire. The book explores the processes of formation and re-formation of citizen bodies, the integration of foreigners, the question of multiple-citizenship holders and the political and philosophical thought on ancient citizenship. The aim is that of offering a multidisciplinary approach to the subject, ranging from literature to history and philosophy, as well as encouraging the reader to integrate the traditional institutional and legalistic approach to citizenship with a broader perspective, which encompasses aspects such as identity formation, performative aspect and discourse of citizenship.